Biocurativo de quitosana e pectina incorporada com extrato de Jatropha multifida. - Souza, Francielly de (2021)
The objective of this study was the production of a bio-egradable bio-healing based on pectin and chitosan incorporated with Jatropha multifida extract for use in cutaneous wounds. For this, the ethanolic extraction was made from the leaves of the plant. In order not to interfere with the transparency of the biodressing, the chlorophyll of the extract was removed with activated charcoal. TLC (Thin Layer Chromatography) confirmed the presence of tannins, flavonoids, terpenes and alkaloids both in the clarified extract and in the extract with chlorophyll. The antimicrobial action of the extracts on Pseudomonas aeruginosa was also proven, producing inhibition halos of 5 to 15 mm. For the formulation of biodressings, different percentages of pectin/chitosan were tested, this step was carried out with commercial pectin by the casting method. The percentages of pectin and chitosan respectively were: 75:25; 50:50 and 25:75 (m/m), the final concentration of polymers in relation to the volume of film-forming solution was 3.7%. The mechanical tests showed an increase in the percentage of deformation from 6% for the film without chitosan to 83% for the one with the highest proportion of chitosan. The infrared spectra showed bands that confirmed the chemical interaction between the polymers. The film chosen for the continuation of the work with the pectin extracted from the orange pomace was 25:75 (pectin/chitosan) for presenting better elongation characteristics in the mechanical tests, good interaction between the polymers demonstrated in the infrared graph, for allowing the passage of water vapor, and present better visual and tactile characteristics and due to the antimicrobial action of chitosan. The extraction of pectin used to formulate the films with Jatropha multifida extract was carried out in an acid form using 0.1 mol.L-1 hydrochloric acid from orange pomace: albedo, albedo/flavedo and albedo/flavedo/vesicles of orange juice. and the yield and degree of esterification respectively were: 12.30% and 40% for albedo pectin, 10.91% and 43% for albedo+flavedo pectin and 10.21% and 46% for albedo pectin +flavedo+juice vesicles, the latter was chosen for the formulation of the films because it allows the reuse of the whole bagasse and presents a degree of esterification closer to that of commercial pectin, used in the first stage of the work. Films with the extracted pectin and clarified extract were prepared with 2% (m/v) of polymers in the preparation of the solution to avoid the formation of lumps. The films obtained were easily removed from the plate and presented a smooth, shiny surface, some bubbles, malleability, transparency, aspects that were observed tactilely and visually. The films formulated from the extracted pectin showed lower tensile strength 0.7 MPa, thus suggesting that the extracted pectin provided a less rigid film. These films showed higher water vapor transmission rates 14.71 and 14.87 g/h.m². The PAFV+chitosan filmogenic solutions with and without extract showed inhibitory action against Pseudomonas aeruginosa. It was possible to develop a film with pectin extracted from whole orange pomace and chitosan incorporated with clarified Jatropha multifida extract with inhibitory capacity against Pseudomonas aeruginosa, making possible studies in the application of skin wounds.